2015
DOI: 10.1080/15548627.2015.1023981
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce autophagy through FOXO1-dependent pathways

Abstract: Autophagy is a catabolic process in response to starvation or other stress conditions to sustain cellular homeostasis. At present, histone deacetylase inhibitors (HDACIs) are known to induce autophagy in cells through inhibition of mechanistic target of rapamycin (MTOR) pathway. FOXO1, an important transcription factor regulated by AKT, is also known to play a role in autophagy induction. At present, the role of FOXO1 in the HDACIs-induced autophagy has not been reported. In this study, we first observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
135
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 67 publications
5
135
1
Order By: Relevance
“…52,54 Interestingly, the refractoriness to HDACi treatment coincides with the premature block of autophagy reported in this work. Recent evidence underscores a role of HDACi in inducing autophagy 55,56 by directly regulating LC3 levels. The HDACi-mediated induction of autophagy has been associated with ROS and damaged mitochondria clearance that imparts a pro-survival effect.…”
Section: Discussionmentioning
confidence: 99%
“…52,54 Interestingly, the refractoriness to HDACi treatment coincides with the premature block of autophagy reported in this work. Recent evidence underscores a role of HDACi in inducing autophagy 55,56 by directly regulating LC3 levels. The HDACi-mediated induction of autophagy has been associated with ROS and damaged mitochondria clearance that imparts a pro-survival effect.…”
Section: Discussionmentioning
confidence: 99%
“…West et al (27) showed that the immune system is absolutely necessary for the anticancer effect of HDACI (9,11,24,28). HDACI distribute to the up-regulation of natural killer NK1-cell activating ligands MHC class I and II, which are responsible for antigen presentation on the surface of cancer cells (22). HDACI can sensitize malignant cells to the antineoplastic effect of IFN-γ by increasing the number of IFN-γ receptors (IFNGR1) on the surface of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It also increases the expression of Il-2, TNF-a, GM-CSF and the activation of T-cells. Moreover, TSA induces autophagy in cells through inhibition of rapamycin motor pathway (22) and inhibits apoptosis of activated CD4 + T lymphocytes (23). Butyrate as well as trichostatin A inhibited the cell growth mainly by arresting the cell cycle and the cell invasion was inhibited by butyrate and trichostatin A.…”
Section: Trichostatin a (Tsa)mentioning
confidence: 99%
See 2 more Smart Citations